AN APPRAISAL OF INSECT SPECIES VISITING SOME ORNAMENTAL PLANTS IN ZARIA, NIGERIA: A CASE STUDY OF AHMADU BELLO UNIVERSITY ZARIA-NIGERIA - Dalhat, I. K.; Abubakar, B. Y.; Abdulaziz, B. K. (FUDMA Journal of Sciences, 2023)
This study was carried out in Ahmadu Bello University, Zaria, Main-campus, Samaru. The study area was divided into four units, the units were surveyed two times, the first survey was in May, 2015 and the second was in July, 2015. On each survey, insects were collected using sweep net from associated ornamental plants in a research unit of a study area independently. Eight species of ornamental plants were surveyed and a total number of ninety insects were collected from the plants and identified. The area of study showed significant difference (p
Keywords: Insects, Pollinators, Ornamental plants, Biodiversity